Effect of High Temperatures on Seeds - Results of a Study with Leucaena leucocephala - Sharma, K. K.; Naithani, K. C.; Sangal, P. M. (Indian Forester, 1985)
High temperatures generated by forest fires have a profound effect on seeds particularly those lying on the forest floor or buried in top layer of the soil. The seeds of different species are known to vary in their tolerance to high temperatures depending on their individual characters chiefly the type of seed coat. While soft seeds are consumed by the fire’ the seeds of some species having hard seed coats actually need fairly high temperatures to break the dormacy and to induce germination. Such variations in heat tolerance behaviour of seeds account for the pattern of vegetational succession following burning of an area. Heat tolerance behaviour of seeds of forest as well as agricultural crops has been studied by many workers abroad but no such work appears to have been done in India. The results of a pilot laboratory trial on the seeds of Leucaena leucocephala are discussed in this paper. It has been found that dry heat treatment of 75Â°-80Â°C for 5 minutes actually increased the germination whereas temperature range of 125Â°-130Â°C for 5 minutes proved lethal for these seeds.